Three new DC-to-DC Single-Switch Converters - Barry W. Williams; Mona Fouad Moussa (Renewable Energy and Sustainable Development)
This paper presents a new family of three previously unidentified dc-to-dc converters, buck, boost, and buck-boost voltage-transfer-function topologies, which offer advantageous transformer coupling features and low capacitor dc voltage stressing. The three single-switch, single-diode, converters offer the same features as basic dc-to-dc converters, such as the buck function with continuous output current and the boost function with continuous input current. Converter time-domain simulations and experimental results (including transformer coupling) support and extol the dc-to-dc converter concepts and analysis presented.